ChemInform Abstract: Rapid Synthesis of Indole cis‐Enamides via Hydroamidation of Indolic Alkynes. Issue 4 (28th January 2014) - Dickson, Emma; Copp, Brent R.; Barker, David
Abstract The selective synthesis of indolic cis‐enamides (VII) and (IX) via ruthenium‐catalyzed hydroamination of indole acetylenes (IV) with primary amides (V) and (VIII), resp.